Construction of a Pea Tendril cDNA Library and Sequence Analysis of a Pea Actin cDNA, PEAcl - 曹晓风 王荣臣 阎隆飞 鲁治滨 潘乃隧 陈章良 (中国科学通报：英文版, 1994)
Actins are ubiquitous to all of the known eukaryotic organisms. Since the firstdiscovery of actins in higher plants by Yen et al. in 1960s, the actin research ofhigher plants has been extensively carried out. It has been shown that the actin is animportant part of cytoskeleton, being involved in many important biological processes,